Evaluation of Student Admission System Using Expressing, Emotions And Experiences (3E) Method - Muhammad Athaillah; Abims Fardiansa; Agung Rizka; Wahyu Andhika Kusuma (Journal of Telematics and Informatics, 2018)
Admission website or well-known as PMB in University of Muhammadiyah Malang is used by millions of people every year. The accessibility of the website for mobile platform should be elevated to meet the standard of modern website by taking note of User Experience (UX) aspect. This study aims to evaluate the prototype of admission website for mobile platform using Expressing, Emotions and Experiences (3E) method. 3E is a self-report method allowing both pictorial and verbal reporting. A set of questionnaires in a form of a paper with human body sketch and a box dialog are compiled and distributed to respondents. The result shows that the prototype has 60% positive responds.